2019
DOI: 10.3390/nano9020158
|View full text |Cite
|
Sign up to set email alerts
|

Latent Heat Storage and Thermal Efficacy of Carboxymethyl Cellulose Carbon Foams Containing Ag, Al, Carbon Nanotubes, and Graphene in a Phase Change Material

Abstract: Carbon foam was prepared from carboxymethyl cellulose (CMC) and Ag, Al and carbon nanotubes (CNTs), and graphene was added to the foam individually, to investigate the enhancement effects on the thermal conductivity. In addition, we used the vacuum method to impregnate erythritol of the phase change material (PCM) into the carbon foam samples to maximize the latent heat and minimize the latent heat loss during thermal cycling. Carbon foams containing Ag (CF-Ag), Al (CF-Al), CNT (CF-CNT) and graphene (CF-G) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…As a result, it is necessary to study the solid–liquid phase change material with NFC aerogel as the supporting material. Kim et al 27 prepared carbon foam by using methyl cellulose (CMC). In addition, the composite PCMs (CPCMs) incorporate erythritol into the cellulose carbon foam by vacuum impregnation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is necessary to study the solid–liquid phase change material with NFC aerogel as the supporting material. Kim et al 27 prepared carbon foam by using methyl cellulose (CMC). In addition, the composite PCMs (CPCMs) incorporate erythritol into the cellulose carbon foam by vacuum impregnation.…”
Section: Introductionmentioning
confidence: 99%
“…Physical blending involves the addition of polyurethane, polyethylene, epoxy, cellulose, graphite, and other inorganic nanoparticles as matrix materials to support PCMs. In addition, cellulose, , silica gel, melamine foam, and aerogels of graphene , are used as containers to infiltrate PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…In another report, Liu et al studied the effect of MWCNTs on the property of pitch derived CF and found that the electrical conductivity of CF increases with increasing MWCNTs but the thermal conductivity first increases then decreases [9] . Kim et al synthesized CF from carboxymethyl cellulose (CMC) and Ag, Al and carbon nanotubes (CNTs), also graphene was added in the foam, then studied the effects of these on the thermal conductivity of CF [10]. Kumar et al, grown MWCNTs on CF by using the method of chemical vapor deposition and found that thermal conductivity of CF rised by 75% due to the addition of MWCNTs [11] .…”
Section: Introductionmentioning
confidence: 99%